Effectiveness of Communication by Corn Agricultural Extension Instructors in Sawerigadi District, West Muna Regency - La Ode Andi Rahmat Mulya (PAPSEL Research and Consulting, 2024)
This research used a quantitative method where the sample consisted of 59 respondents who were divided into two villages, namely Marobea Village with 37 respondents and Lakalamba Village with 22 respondents. The SPSS version 21 program was used to analyze the effectiveness of communication between corn planting teachers. The results of the analysis show that (1) the overall level of farmer participation in agricultural extension activities is included in the less active category. Compared to the participation stage, farmers are more active in implementation than planning. Corn farmers in Marobea Village are more active than corn farmers in Lakalamba Village. (2) Agricultural extension communication between corn farmers in Marobea and Lakalamba Villages is most effective in increasing knowledge (cognitive) and subsequently influencing attitudes (affective), but less effective in encouraging action tendencies (behavioral). Extension communication between corn farmers in Marobea Village is more effective compared to corn farmer groups in Lakalamba Village. The more active farmers are, the more motivated they are to apply extension materials. and (3) Factors that determine the effectiveness of extension communication include extension factors, extension methods, and facilities and infrastructure. Extension factors related to the effectiveness of extension communication are the attitude, communication and knowledge aspects of the instructor. Aspects of method suitability and effectiveness are also related to the effectiveness of extension communication which is supported by the availability of extension infrastructure.